Cell-penetrating peptide modified AIE polymeric nanoparticles by miniemulsion polymerization and application for cell fluorescence imaging. Issue 30 (3rd July 2019) - Hu, Yaxin; Liang, Xiaoqin; Zhuang, Zeyan; Cao, Zhihai; Qi, Qi; Wang, Yijia; Mi, Yifang; Zhao, Zujin; Cui, Qinmin
Abstract : AIE polymeric nanoparticles surface-modified with HIV Tat peptides for cell fluorescence imaging are efficiently prepared through miniemulsion polymerization, carbodiimide reaction, and thiol-maleimide click reaction in sequence. Abstract : Surface modification with bioactive groups is critical to the advanced bio-application of fluorescent nanoparticles (NPs), because it may offer specific interaction between the NPs and tissues, cells, as well as organelles. In this work, amino-functionalized aggregation-induced emission (AIE) polymeric NPs (AIE-PNPs) were efficiently synthesized through a one-pot miniemulsion copolymerization of methyl methacrylate and an amino-containing functional comonomer. The AIE-PNPs displayed a well-defined spherical morphology with a sub-100 nm particle size, and narrow particle size distribution. The surface of AIE-PNPs was further modified with maleimide groups and HIV-1 Tat peptides through a sequential carbodiimde reaction and a thiol-maleimide click reaction. The peptide-modified AIE-PNPs displayed good photostability and colloidal stability under continuous light irradiation or under various pH values, as well as good storage stability in aqueous media. The cell uptake efficiency of AIE-PNPs was significantly improved by the surface modification of HIV-1 Tat peptides, achieving good cell fluorescence imaging quality at a relatively low AIE-PNP concentration.